Successful surgical closure of an aortopulmonary window associated with Holt-Oram syndrome in adulthood - Milić, Aleksa Z; Stefanović, Igor; Matejić, Kristina; Jovanović, Ida (Vojnosanitetski pregled, 2021)
Abstract Introduction. Aortopulmonary window (APW) is a rare congenital anomaly caused by incomplete division of the embryonic common arterial trunk which allows direct and usually unobstructed communication between the ascending aorta and pulmonary artery trunk. Holt-Oram syndrome (HOS) is an autosomal dominant disorder caused by the mutation in the TBX5 gene and it is characterized by bones abnormalities in at least one limb while the association with APW is extremely rare. Case report. We report a case of a female patient in her thirties with an extremely rare combination of the HOS and APW window that reached the adulthood without surgical correction. The adult patient came to our clinic with signs of severe heart failure and pulmonary hypertension. Although previously diagnosed as inoperable, after the decongestive medical treatment and detailed diagnostic procedures we proved reactive pulmonary vascular resistance and the patient was successfully surgically treated. Conclusion. This case confirms the absolute necessity of cautious and comprehensive examinations of each patient with congenital heart disease and pulmonary hypertension irrespective of age.